Variations in candidalysin amino acid sequence influence toxicity and host responses. - Sullivan, Derek (My University, 2024)
Candida albicans causes millions of mucosal infections in humans annually. Hyphal overgrowth on mucosal surfaces is frequently associated with tissue damage caused by candidalysin, a secreted peptide toxin that destabilizes the plasma membrane of host cells thereby promoting disease and immunopathology. Candidalysin was first identified in C. albicans strain SC5314, but recent investigations have revealed candidalysin "variants" of differing amino acid sequence in isolates of C. albicans, and the related species C. dubliniensis, and C tropicalis, suggesting that sequence variation among candidalysins may be widespread in natural populations of these Candida species. Here, we analyzed ECE1 gene sequences from 182 C. albicans isolates, 10 C. dubliniensis isolates, and 78 C. tropicalis isolates and identified 10, 3, and 2 candidalysin variants in these species, respectively. Application of candidalysin variants to epithelial cells revealed differences in the ability to cause cellular damage, changes in metabolic activity, calcium influx, MAPK signalling, and cytokine secretion, while biophysical analyses indicated that variants exhibited differences in their ability to interact with and permeabilize a membrane. This study identifies candidalysin variants with differences in biological activity that are present in medically relevant Candida species. Importance: Fungal infections are a significant burden to health. Candidalysin is a toxin produced by Candida albicans that damages host tissues, facilitating infection. Previously, we demonstrated that candidalysins exist in the related species C. dubliniensis and C. tropicalis, thereby identifying these molecules as a toxin family. Recent genomic analyses have highlighted the presence of a small number of candidalysin "variant" toxins, which have different amino acid sequences to those originally identified. Here, we screened genome sequences of isolates of C. albicans, C. dubliniensis, and C. tropicalis and identified candidalysin variants in all three species. When applied to epithelial cells, candidalysin variants differed in their ability to cause damage, activate intracellular signaling pathways, and induce innate immune responses, while biophysical analysis revealed differences in the ability of candidalysin variants to interact with lipid bilayers. These findings suggest that intraspecies variation in candidalysin amino acid sequence may influence fungal pathogenicity.
PUBLISHED
Keywords: Candida, candidalysin, epithelial, fungus, toxin; Genes & Society; Immunology, Inflammation & Infection; CANDIDA ALBICANS; Genomes, Genomics; Molecular Biology; Mycology and fungal pathogenesis